Qur'an : a historical-critical introduction - Sinai, Nicolai, 1976- (New Edinburgh Islamic surveys., 2017)
This comprehensive introduction to the basic methods and current state of historical-critical Qur'anic scholarship covers all of the field's major questions, giving readers the tools needed to work with and understand this vital but complex text.